Discovering wines - Simon, Joanna (Reed Consumer Books, 2015)
This beginner's guide to wine dispels the mystique surrounding the subject and takes a practical approach to tasting, storing, choosing and serving wine. It looks at the processes involved in creating a first-class wine and the most important wine-producing regions and names across the world.